Peningkatan Aspek Perkembangan Moral Anak Usia Dini Melalui Metode Pembiasaan di TK Islam Al-Husna Samarinda - Apriansyah, Adam Hasyim; Febryan, Muhammad Dimas; Milsan, Haidar; Anwar, Aida Choirul; Nedriyan, Huli Sabpa; Qomariah, Siti; Isnawati, Isnawati (Faculty of Education and Teacher Training of UINSI Samarinda, 2025)
Moral education in early childhood is a critical foundation for developing positive character traits such as discipline, empathy, and responsibility. However, the application of habituation methods to strengthen children’s moral aspects in early childhood education settings has not been thoroughly explored. This study aims to optimize the reinforcement of moral aspects in early childhood through habituation methods implemented at TK Islam Al-Husna Loa Bakung. The research employed a classroom action research (CAR) design conducted in two cycles, each consisting of planning, implementation, observation, and reflection stages. The subjects were students of TK Islam Al-Husna, with data collected through observation, interviews, and documentation. Analysis was carried out using a qualitative approach. The results demonstrated significant improvement across five moral indicators: religious awareness (from 71.25% to 93.7%), sharing and caring, respecting others, honesty, and responsibility. Habituation methods, such as collective prayers, role modeling by teachers, and positive corrections, were proven effective in consistently improving children’s morals. Habituation methods serve as an effective approach to enhancing the moral aspects of early childhood. The findings of this study offer practical contributions to the development of character education in schools.